Using progress logs to research the information behaviour of higher education students in prison - Isabel Virgo (Information Research: An International Electronic Journal)
Introduction. This short paper introduces 'progress logs', an adaptation of the solicited diary method, and details their planned use in a forthcoming study on the information behaviour of students in transition from prison to higher education.